Partial microduplication in the histone acetyltransferase complex member KANSL1 is associated with congenital heart defects in 22q11.2 microdeletion syndrome patients - Luis E. León; Felipe Benavides; Karena Espinoza; Cecilia Vial; Patricia Alvarez; Mirta Palomares; Guillermo Lay-Son; Macarena Miranda; Gabriela M. Repetto (Scientific Reports, 2017)
Abstract 22q11.2 microdeletion syndrome (22q11.2DS) is the most common microdeletion disorder in humans, with an incidence of 1/4000 live births. It is caused by a heterozygous deletion of 1.5–3 Mb on chromosome region 22q11.2. Patients with the deletion present features that include neuropsychiatric problems, craniofacial abnormalities and cardiovascular malformations. However, the phenotype is highly variable and the factors related to the clinical heterogeneity are not fully understood. About 65% of patients with 22q11.2DS have congenital heart defects (CHD). The main goal of this study was to identify common CNVs in 22q11.2DS patients that could be associated with the incomplete penetrance of CHD. Analysis of genomic DNA from 253 patients with 22q11.2DS using array technology showed an association between a microduplication located in region 17q21.31 and CHD (p-value = 0.023, OR = 2.75, 95% CI = 1.17–7.03). This region includes the first three exons of KANSL1 gene. Bioinformatic analysis showed that KANSL1 and CRKL, a gene in the commonly deleted region of 22q11.2DS, are part of the same regulatory module in a miRNA-mRNA network. These results show that a KANSL1 microduplication, in combination with the 22q11.2 deletion, is associated with increased risk of CHD in these patients, suggesting that KANSL1 plays a role as a modifier gene in 22q11.2DS patients.